The effect of corporate diversification on firm value : an emphirical assessment of the JSE securities exchange listed companies - Weldeslassie, Samson (Department of Finance and Tax, 2016)
This paper examines the value effect corporate diversification on firms listed on the JSE Exchange. The value gain or loss for the diversified firms is measured using Berger and Ofek's (1995) model that estimates the value of diversified companies' segments as though they were independent companies. The result indicates corporate diversification in South Africa is value enhancing. Evidence shows that sample of diversified companies are traded, on average, 39-57 (Excess Value 0.33 to 0.45) percent above the industry averages. The value gain is higher in related-diversification than unrelated ones. A similar assessment of a sample of 57 focused companies showed a much lower Excess Value (EV). The EV for diversified companies (0.33 - 0.45) is higher than the EV for focused companies (0.00 - 0.19) suggesting that diversified companies are traded at premium as compared to focused companies. Further analysis of the result shows that the value gain is higher in the medium sized sample companies as compared to the bigger companies. Regression of the EV in relation to firms' characteristics (number of segments per company, capital expenditure, and profitability) showed no significant relationship. To explain the possible sources for higher premium shown in diversified companies, analysis of the companies leverage and tax rate shows that diversified companies have, on average 13% lower debt-to-assets ratio and pay 4.13% lower tax rate than focused companies. It suggests that higher leverage, which gives companies greater tax shield, is not one the sources for the observed higher premium. It, however, indicates that a lower tax derived by combining businesses with imperfectly correlated cash flows can be one of the contributing factors for the value gain. A comparison of Price-to-Earning and Price-to-Book value ratios for the sample diversified and focused companies suggests, in contradiction with the above results, that focused companies perform better than diversified companies.